Pengembangan Laboratorium Lapangan Agribisnis sebagai Unit Usaha dan Pusat Pembelajaran Agripreneurship: Development of Agribusiness Field Laboratory as a Business Unit and Agripreneurship Learning Center - Hartati, Hartati; Ma'mun, Sitti Rahma; Nur, Muhammad; Syaf, Hasbullah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The development of the Agribusiness Field Laboratory (LLA) as a business unit and agripreneurship learning center aims to integrate education, research, and business practices in the agribusiness sector at the University of Muhammadiyah Kendari The development of the LLA began with the installation of a greenhouse, the creation of six NFT hydroponic units, the development of organic cultivation covering an area of 0.5 hectares, and training in the provision of organic fertilizers and botanical pesticides and vermicompost. The results obtained in the first two months of the initial production stage in the hydroponic unit were IDR 4,062,500 and from the organic garden IDR 3,584,000. Investment assessment based on NPV analysis obtained a value of 169,456,788.54. Based on the calculation results above, it can be seen that NPV> 1 so that the hydroponic business with the NFT system meets the requirements as a productive business unit that can increase partner income through campus business development programs.